2021
DOI: 10.21203/rs.2.22946/v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A hybrid cost-sensitive ensemble for heart disease prediction

Abstract: Background: Heart disease is the primary cause of morbidity and mortality in the world. It includes numerous problems and symptoms. The diagnosis of heart disease is difficult because there are too many factors to analyze. What's more, the misclassification cost could be very high. Methods: A cost-sensitive ensemble method was proposed to improve the efficiency of diagnosis and reduce the misclassification cost. The proposed method contains five heterogeneous classifiers: random forest, logistic regression, su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…From the results, it is found that existing methods like RF showed E value as 80.43%, precision as 75.52%, recall as 60.19%, G-mean as 71.04, MC as 87.93%, specificity as 86.34% and AUC as 74.07%. On the other hand, traditional methods like LR, SVM, ELM, KNN and [36] showed better results concerning all the metrics. However, in comparison with the proposed system, existing methods showed low performance.…”
Section: 2performance Analysismentioning
confidence: 92%
See 3 more Smart Citations
“…From the results, it is found that existing methods like RF showed E value as 80.43%, precision as 75.52%, recall as 60.19%, G-mean as 71.04, MC as 87.93%, specificity as 86.34% and AUC as 74.07%. On the other hand, traditional methods like LR, SVM, ELM, KNN and [36] showed better results concerning all the metrics. However, in comparison with the proposed system, existing methods showed low performance.…”
Section: 2performance Analysismentioning
confidence: 92%
“…In addition, proposed and conventional systems are analyzed in the Hungarian dataset. The obtained outcomes are presented in Table 8 [36]. From the results, it is found that existing methods like RF showed E value as 80.43%, precision as 75.52%, recall as 60.19%, G-mean as 71.04, MC as 87.93%, specificity as 86.34% and AUC as 74.07%.…”
Section: 2performance Analysismentioning
confidence: 95%
See 2 more Smart Citations